A Porous SiC Mat for a Gas Radiation Application by Melt-Blown of the Polycarbosilane - Shin, Dong-Geun; Cho, Kwang-Youn; Riu, Doh-Hyung (Asian Journal of Chemistry, 2012)
A porous SiC mat was fabricated by melt blown, curing and pyrolysis of a rheology controlled polycarbosilane. Polycarbosilane has undergone the two step polymerization to get the proper rheology for melt blown. The SiC fibers derived from KNAl-0002 were randomly distributed and stacked layer by layer. The melt blown mat was pressed down at low pressure of 0.2-0.4 kg/cm2 during the curing process to build physical connections among the fibers and finally formed chemical bonds at the contact points after pyrolysis. The neck was also formed among the fibers in the crossing or parallel patterns. In the bending test, the SiC mat was restored to the initial shape after the removal of the compressive load under 50 g. The oxidation layer constantly formed on the fiber periphery without any cracks or pores at the boundaries was considered to be an excellent thermal protective layer. Infra-red radiation effect was also investigated in the fuel gas firing using a commercial gas burner.